2022
DOI: 10.1038/s41598-022-12734-z
|View full text |Cite
|
Sign up to set email alerts
|

Vascular alterations among male elite athletes recovering from SARS-CoV-2 infection

Abstract: SARS-CoV-2 may affect the cardiovascular system and vascular impairment has been reported in healthy young adults recovering from COVID-19. However, the impact of SARS-CoV-2 infection on the vascular function of elite athletes is unknown. We examined 30 healthy male elite athletes (age 25.8 ± 4.6 years) pre-season and at a 6-month follow-up (182 ± 10 days). Vascular function and central blood pressure were calculated using transfer function-based analysis of peripheral arterial waveforms obtained by oscillomet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 42 publications
(61 reference statements)
0
12
0
Order By: Relevance
“…Comparison of vascular changes in male elite athletes recovering from COVID-19 versus uninfected individuals showed a decline of vascular and endothelial function in athletes despite the excellent fitness levels of the participants and the mild course of COVID-19 infection. These results suggest that the infection may affect not only cardiac function but may detrimentally affect aortic reservoir function, resulting in an increase in arterial stiffness, consequently, increasing cardiac work [ 3 ].…”
Section: Cardiac Changesmentioning
confidence: 99%
See 2 more Smart Citations
“…Comparison of vascular changes in male elite athletes recovering from COVID-19 versus uninfected individuals showed a decline of vascular and endothelial function in athletes despite the excellent fitness levels of the participants and the mild course of COVID-19 infection. These results suggest that the infection may affect not only cardiac function but may detrimentally affect aortic reservoir function, resulting in an increase in arterial stiffness, consequently, increasing cardiac work [ 3 ].…”
Section: Cardiac Changesmentioning
confidence: 99%
“…Meanwhile, the long-term COVID-19 symptoms (post-recovery) may be nonspecific and include cough, tachycardia, severe fatigue, ventricular arrhythmias, chest pain, decreased exercise tolerance and depression [ 16 ]. In terms of cardiovascular assessment, it is important to include specialized blood panel, resting electrocardiogram (ECG), 24-h ECG, echocardiogram, cardiopulmonary exercise test, assessment of flow-mediated dilation and CMR [ 3 , 4 ]. The CMR has been used to detect congestive heart failure, cardiac tamponade, and acute myocardial infarction.…”
Section: Clinical Features and Screeningmentioning
confidence: 99%
See 1 more Smart Citation
“…As more and more data are pointing i the same direction, guidelines on a return-to-play protocol tend to be less strict in terms of cardiovascular examination of the athletes [ 26 ]. On the other hand, some authors found that COVID-19 infection might lead to mild vascular impairment, affecting athletic performance [ 27 ]. As there is a lack of data about short-term reinfection in the population of elite athletes, we believe that should not discard the importance of a return to play examination protocol.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, these abnormalities have persisted on follow-up cardiac magnetic resonance imaging after COVID-19 recovery, with the most frequent cardiac changes being myocarditis, regional scar, and pericardial enhancement 21 . Furthermore, studies have shown a decline in vascular and endothelial function in infected athletes, despite excellent fitness levels and mild symptoms, suggesting that COVID-19 inoculation may affect cardiac and aortic reservoir function, which altogether can increase arterial stiffness and cardiac work 20 . How these changes fit in the context of the normal cardiac remodeling seen in athletes is not fully understood and warrants continued investigation.…”
Section: Team Approachmentioning
confidence: 99%